T-way strategy for sequence input interactions test case generation adopting fish swarm algorithm - Rahman, Mostafijur; Sultana, Dalia; Sabira, Khatun; M. F. M., Jusof; Syamimi Mardiah, Shaharum; Nurhafizah, Abu Talip Yusof; Qaiduzzaman, Khandker M.; Hasan, Md. Hasibul; Rahman, Md. Mushfiqur; Hossen, Md. Anwar; Begum, Afsana (Universiti Malaysia Pahang, 2019)
In Combinatorial Input Interaction (CII) based system, the increasing number of input event causes the increasing number of test cases. Since twenty years many useful t-way strategies have been developed to reduce test case size. In order to reduce test cases several T-way sequence input interaction strategies are explored, such as, Bee Algorithm(BA), Kuhn encoding (K) , ASP with Clasp , CP with Sugar, Erdem (ER) exact encoding, Tarui (TA) Method, U, UR, D and DR, Brain (BR). However, none of them claim that for all test configuration the produced test cases are best. The reason is that the T-way sequence input interaction is NP-Hard problem. In this research, Fish Swarm algorithm is proposed to adapt with T-way sequence input interaction test strategy. The proposed system is compared with the other renowned search-based Tway strategies. The result shows that the proposed system is able to generate feasible and optimal results.